2005
DOI: 10.2458/azu_rangelands_v27i1_waldron
|View full text |Cite
|
Sign up to set email alerts
|

Forage Kochia—Uzbekistan's Desert Alfalfa

Abstract: Forage kochia germplasm from Uzbekistan may increase fall and winter grazing and habitat for livestock and wildlife on western rangelands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
0
7
1
1
Order By: Relevance
“…The breeding of Snowstorm was initiated via a germplasm exchange trip by B. L. Waldron to Uzbekistan in October 2002. Twenty‐two collections of forage kochia were obtained during this trip (Waldron et al, 2005) and brought back to Logan, UT for evaluation. Snowstorm traces its parentage to one of these collections (NPGS no.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The breeding of Snowstorm was initiated via a germplasm exchange trip by B. L. Waldron to Uzbekistan in October 2002. Twenty‐two collections of forage kochia were obtained during this trip (Waldron et al, 2005) and brought back to Logan, UT for evaluation. Snowstorm traces its parentage to one of these collections (NPGS no.…”
Section: Methodsmentioning
confidence: 99%
“…PARL 418), which possibly included seed from remnant plants of the Uzbek landrace/population called Otavny. Otavny was described by researchers from the Uzbek Research Institute of Karakul Sheep Breeding and Ecology of Deserts in Samarkand, Uzbekistan as an ecotype‐specific population of the subspecies grisea ( canescens , or stony variety) originating from the foothills of the Kirghizia region; it was collected using mass selection and characterized as very productive with unique regrowth potential (Waldron et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For centuries, forage kochia has been an important fall and winter forage for sheep, cattle, horses, camels, and wildlife in Kazakhstan, Uzbekistan, and surrounding republics (Balyan, 1972;Waldron et al, 2005Waldron et al, , 2010. In the United States, Waldron et al (2006) recently reported that cattle grazing Immigrant forage kochia during the fall and winter maintained or improved body condition without any additional protein or nutrient supplementation.…”
mentioning
confidence: 99%